1986
DOI: 10.1111/j.1365-2621.1986.tb13073.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Content and Sensory Analysis of Ground Beef as Influenced by Fat Level, Heating, and Storage

Abstract: Twelve treatment combinations including three fat levels, two internal endpoint temperatures, and two storage periods for ground beef patties were studied. Quality and sensory attributes as well as cholesterol content were evaluated. As fat level increased in raw patties, cholesterol content, drip and total cook loss, fat and cholesterol content of cook drip increased whereas red color intensity and evaporative losses decreased. Cholesterol content, evaporative and total losses, and beefflavor intensity increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
4
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 5 publications
10
64
4
1
Order By: Relevance
“…The reports in the scientific literature related to irradiation effects on sensory characteristics of foods are controversial. Kregel et al (1986) did not observe significant difference (p40.05) in sensory attributes between irradiated and non-irradiated burgers. Murano et al (1998) also did not find any significant alterations between non-irradiated frozen burgers and those irradiated at 2 kGy.…”
Section: Article In Presscontrasting
confidence: 57%
“…The reports in the scientific literature related to irradiation effects on sensory characteristics of foods are controversial. Kregel et al (1986) did not observe significant difference (p40.05) in sensory attributes between irradiated and non-irradiated burgers. Murano et al (1998) also did not find any significant alterations between non-irradiated frozen burgers and those irradiated at 2 kGy.…”
Section: Article In Presscontrasting
confidence: 57%
“…Although the current study demonstrated few differences during blind testing of ground beef patties varying in fat level, previous authors have reported differences in multiple palatability traits. Higher- fat ground beef has been observed to have greater tenderness compared with lower-fat formulations (Cross et al, 1980;Berry and Leddy, 1984;Kregel et al, 1986;Garzon et al, 2003). Also, similar to the current study, ground beef with higher fat has been well documented as having higher juiciness ratings than low-fat ground beef (Cross et al, 1980;Huffman and Egbert, 1990;Miller et al, 1993;Blackmon et al, 2015).…”
Section: Effect Of Fat Level On Palatability Ratings Of Ground Beefsupporting
confidence: 72%
“…Salamis containing 2% IPaO showed the least fat content. The lower fat content of controls compared to samples to which IPO was added may be due to unextractable connective tissues found in beef fat and weighted as fat in preparing the formulations [10] and also the higher initially moisture content of beef fat [24]. Liu et al [24] also noted that ground beef containing hydrogenated cottonseed, palm and soybean oil had a slightly higher fat content than patties made with beef fat.…”
Section: Chemical and Physical Compositionmentioning
confidence: 94%
“…Fat plays an important role on binding, rheological and structural properties, and especially formation of stable meat emulsions in meat products such as frankfurters and salamis [9], so technological aspects associated with the processing of low-fat meat products included problems with the texture, flavour and mouthfeel [10][11][12][13][14]. Many non-meat ingredients such as water [11], carbohydrates [9,13,[15][16][17][18], soy protein [19] and plant oils [4,[20][21][22] have been added to different meat products to counteract the problems caused by fat reduction.…”
Section: Introductionmentioning
confidence: 99%